Electrolyte for inhibiting cyclic gas production of sodium-ion battery as well as preparation method and application of electrolyte
By using electrolyte containing cyanosiloxane-based functional additives in sodium ion batteries, the serious gas production problem during the circulation of sodium ion batteries is solved, and the battery capacity retention rate and cycle life are significantly improved.
Patent Information
- Application Number
- CN202411378603.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-03-14
AI Technical Summary
There are serious gas production problems during the circulation of sodium ion batteries, resulting in low cycle life of multiplier discharge.
An electrolyte containing cyanosiloxane-based functional additives is used to react with H2O to generate amino groups, remove water and reduce the damage of the positive electrode material; its anionic groups are adsorbed on the surface of the positive electrode to reduce the contact surface between the electrolyte and the positive electrode; there is a strong interaction with HF, which captures H protons and removes corrosive HF, and protects the positive electrode material.
It significantly improves the capacity retention rate of sodium ion batteries, extends the rate discharge cycle life, and suppresses gas production under high temperature cycles.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to an electrolyte for inhibiting cyclic gas generation of a sodium ion battery, and a preparation method and application thereof. Background Art
[0002] Lithium resources are unevenly distributed, mainly concentrated in the Americas and other regions. It is predicted that by 2025, the demand for lithium carbonate will increase sharply, and there will be a huge raw material gap. Compared with lithium-ion batteries, sodium-ion batteries can reduce costs by 30% to 40%, with obvious cost advantages. In addition, sodium resources are abundant, and there is no risk of strategic resources. The main advantages of sodium-ion batteries are high and low temperature performance, rate performance and safety. The mainstream development in the future will mainly be used in energy storage electric two-wheeled vehicles and low-speed vehicles. Judging from the current research and development results, the energy density of sodium-ion batteries is higher than that of lead-acid batteries, and is now basically on par with lithium iron phosphate batteries. The main problem of layered oxides in the positive electrode materials of sodium ion batteries is that their structural stability is relatively poor, and they are prone to gas production, which leads to a low rate discharge cycle life of sodium ion batteries. The gas production of layered oxide sodium ion batteries includes gas production during the formation process and gas production during later charging and long-term storage. The main reasons for gas production are the side reaction of residual alkali on the surface of the positive electrode material, the reduction of trace water in the electrolyte, the electrochemical reduction of solvent molecules on the negative electrode side, and the side reaction of the negative electrode reduction products with solvent molecules when the battery is stored in a charged state for a long time.
[0003] Therefore, it is imperative to provide an electrolyte to improve the rate discharge cycle life of layer oxygen system sodium ion batteries. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes an electrolyte for inhibiting the gas generation of sodium ion batteries during circulation. After using the electrolyte containing a functional additive of cyanosiloxane, the capacity retention rate of the battery is significantly improved.
[0005] A second aspect of the present invention provides a method for preparing an electrolyte.
[0006] According to a third aspect of the present invention, a sodium ion battery is provided, comprising a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte.
[0007] According to the first aspect of the present invention, an electrolyte for inhibiting cyclic gas generation in a sodium ion battery comprises, by weight, 80 to 85 parts of a carbonate organic solvent, 0.5 to 5 parts of a negative electrode film-forming additive, and 0.5 to 2.5 parts of a cyanosiloxane multifunctional additive;
[0008] The structural formula of the cyanosiloxane multifunctional additive is shown in Formula I:
[0009] R1, R2 and R3 are each independently selected from H, F, C1-C4 chain alkyl and C1-C4 perfluoroalkyl;
[0010]
[0011] According to the embodiments of the first aspect of the present invention, there are at least the following beneficial effects:
[0012] Based on the serious gas generation problem of the layered oxide system of sodium ion batteries during the cycle and high-temperature cycle, a cyanosilane additive is added to the electrolyte system of the present invention, wherein the additive contains a cyano group, which can react with H2O to generate an amino group, thereby removing water and reducing the NaNi x Fe y Mn (1-x-y) The NaOH and Na2CO3 produced by the contact of water and air in the O2 positive electrode material have a destructive effect on the positive electrode side of the battery, and reduce the gas generation behavior caused by the presence of residual alkali on the surface. The anionic groups of this type of additive have high electronegativity and can be adsorbed on the positive electrode surface, reducing the contact area between the electrolyte and the positive electrode, and playing a barrier effect; at the same time, there is a strong interaction between this type of additive and HF, capturing H protons, removing corrosive HF, inhibiting the corrosion of HF on the electrode material under high voltage, and can better protect NaNi x Fe y Mn (1-x-y) O2 positive electrode material, to prevent the electrolyte from being decomposed by oxidation and reduction on the surface of the active material; cyanosiloxane additives can generate a more stable NaF-rich high ion conductivity interface film SEI layer on the negative electrode, which can prevent the negative electrode material from peeling off at high temperature. Reduce the active Na consumed by the destruction and repair of the SEI film + , thereby increasing the reversible insertion and extraction of Na + The content reduces the number of defect sites in the hard carbon, reduces the adverse side reactions between the electrolyte and the hard carbon at the interface, maintains a relatively stable impedance of the negative electrode, improves the first coulomb efficiency of the hard carbon negative electrode, and increases the rate discharge cycle life of the sodium ion battery.
[0013] According to some embodiments of the present invention, the cyanosiloxane multifunctional additive includes: at least one of 2-cyanoethyltriethoxysilane, 3-diethoxysilylpropionitrile, 4-triethoxysilylbutyronitrile, 2-cyanoethylmethyldiethoxysilane, 3-(trimethoxysilyl)propionylnitrile, 3-propionitrile tributylmethoxysilane, 3-[tris(2,2,2-trifluoroethoxy)silyl]propionitrile and 5-triethoxysilylvaleronitrile.
[0014] According to some embodiments of the present invention, the structural formula of 2-cyanoethyltriethoxysilane is shown in II:
[0015]
[0016] According to some embodiments of the present invention, the structural formula of the 3-diethoxysilylpropionitrile is shown in III:
[0017]
[0018] According to some embodiments of the present invention, the structural formula of the 4-triethoxysilyl butyronitrile is shown in IV:
[0019]
[0020] According to some embodiments of the present invention, the structural formula of the 2-cyanoethylmethyldiethoxysilane is shown in V:
[0021]
[0022] According to some embodiments of the present invention, the structural formula of the 3-(trimethoxysilyl)propionyl nitrile is shown in VI:
[0023]
[0024]
[0025] According to some embodiments of the present invention, the structural formula of the 3-propionitrile tributylmethoxysilane is shown in VII:
[0026]
[0027] According to some embodiments of the present invention, the structural formula of the 3-[tris(2,2,2-trifluoroethoxy)silyl]propionitrile is shown in IX:
[0028]
[0029] According to some embodiments of the present invention, the structural formula of the 5-triethoxysilylvaleronitrile is shown as X:
[0030]
[0031] According to some embodiments of the present invention, the negative electrode film-forming additive includes at least one of fluoroethylene carbonate (FEC), diethylene sulfate (DTD) and 1-3 propene sultone (PS).
[0032] According to some embodiments of the present invention, the carbonate organic solvent includes at least one of a cyclic carbonate and a linear carbonate.
[0033] According to some embodiments of the present invention, the cyclic carbonate includes at least one of ethylene carbonate and propylene carbonate.
[0034] According to some embodiments of the present invention, the linear carbonate includes at least one of diethyl carbonate and ethyl methyl carbonate.
[0035] According to some embodiments of the present invention, the raw material for preparing the electrolyte further includes electrolyte sodium salt, and the electrolyte sodium salt includes: sodium hexafluorophosphate.
[0036] According to some embodiments of the present invention, the raw materials for preparing the electrolyte include, by weight, 80 to 85 parts of a carbonate organic solvent, 10 to 15 parts of an electrolyte sodium salt, 0.5 to 5 parts of a negative electrode film-forming additive, and 0.5 to 2.5 parts of a cyanosiloxane multifunctional additive.
[0037] According to an embodiment of the second aspect of the present invention, a method for preparing an electrolyte is provided. The method comprises mixing raw materials for preparing the electrolyte.
[0038] According to some embodiments of the present invention, the mixing process is performed in a glove box, and environmental indicators in the glove box include: H2O<0.1ppm.
[0039] According to some embodiments of the present invention, the method for preparing the electrolyte comprises the following steps:
[0040] S1. In a glove box filled with high-purity argon, the moisture in the glove box is controlled to be below 0.1ppm. First, the following components are weighed in parts by weight: 80-85 parts of a non-aqueous organic solvent, 10-15 parts of an electrolyte sodium salt, 0.5-5 parts of a negative electrode film-forming additive, and 0.5-2.5 parts of a functional additive;
[0041] S2. dissolving the electrolyte sodium salt in a non-aqueous organic solvent and stirring to form a uniform solution;
[0042] S3. Then add the film-forming additives and functional additives one by one into the uniform solution described in step S2, and stir to obtain an electrolyte.
[0043] According to an embodiment of the third aspect of the present invention, a sodium ion battery is provided, wherein the lithium ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte.
[0044] According to some embodiments of the present invention, the positive electrode comprises a layered oxide NaNi x Fe y Mn (1-x-y) O2.
[0045] There is a strong interaction between cyanosilane additives and HF, which captures H protons, removes corrosive HF, reduces the decomposition of FEC, inhibits the corrosion of HF on electrode materials under high voltage, and inhibits its interaction with NaNi x Fe y Mn (1-x-y) The side reactions of residual alkali Na2CO3 and NaOH on the surface of O2 active materials and the side reactions with the electrolyte further inhibit the dissolution of transition metal ions and are beneficial to the NaNi x Fe y Mn (1-x-y) The structural stability of the O2 material prevents the O3 phase from + The embedding / extraction process is accompanied by complex phase changes (multiple platforms). The phase change process causes volume changes in the material structure, resulting in distortion and collapse of the layered structure, which affects the battery cycle stability. When the P2 structure with a low Na content is charged to high voltage (O3 and P2 phases are two different structural forms of NaNixFeyMn(1-xy)O2 materials, which differ according to the coordination configuration of Na+ and the stacking mode of oxygen), the sodium content in the crystal structure is too low, making Na + The shielding effect on oxygen atoms weakens, and the electrostatic repulsion between adjacent oxygen atoms causes the adjacent transition metal layers to slide, forming a transition from the P2 phase to the O2 phase. The phase transition will lead to excessive volume changes, showing severe capacity decay in fewer cycles, further inhibiting the occurrence of gas generation.
[0046] According to some embodiments of the present invention, the negative electrode includes at least one of hard carbon, titanium-based sodium oxide metal, and the like.
[0047] According to some embodiments of the present invention, the negative electrode comprises hard carbon.
[0048] Reduces the active Na consumed by the destruction and repair of SEI film + , thereby increasing the reversible insertion and extraction of Na + The content reduces the number of defect sites in the hard carbon, reduces the adverse side reactions between the electrolyte and the hard carbon at the interface, maintains a relatively stable impedance of the negative electrode, improves the first coulomb efficiency of the hard carbon negative electrode, and improves the rate discharge cycle life of the layered oxygen system sodium ion battery.
[0049] The electrolyte for inhibiting gas production of sodium ion battery with the cyanosiloxane multifunctional additive of the present invention is applied to a high voltage sodium ion battery system, wherein the positive electrode active material of the high voltage sodium ion battery is NaNi x Fe y Mn (1-x-y)O2, hard carbon is used for the negative electrode, and the electrolyte containing the additive is injected into the soft pack battery to evaluate the high temperature (55°C) cycle performance of this electrolyte system that inhibits gas production, and the electrolyte containing the additive is injected into the cylindrical battery to evaluate the normal temperature (25°C) cycle performance and low temperature (-20°C) discharge performance of this electrolyte system that inhibits gas production. The normal temperature and high temperature cycle performance tests are carried out at a charge and discharge rate of 1C within the voltage range of 2.0-4.15V. The battery capacity retention rate and battery volume expansion rate are recorded for 1500 cycles for comparison, and the low temperature (-20°C) discharge performance rate is 0.5C.
[0050] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be obvious from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION
[0051] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0052] Example 1
[0053] This embodiment provides an electrolyte and a preparation method thereof, specifically:
[0054] The battery electrolyte is composed of raw materials as shown in Table 1;
[0055] The electrolyte and the preparation method thereof are:
[0056] A1. In a glove box filled with high-purity argon, the moisture in the glove box is controlled below 0.1 ppm, and the raw materials for preparing the electrolyte are weighed respectively;
[0057] A2. Then dissolve the electrolyte sodium salt in a carbonate organic solvent and stir to form a uniform solution;
[0058] A3. Add the negative electrode film-forming additive and the cyanosiloxane multifunctional additive one by one to the uniform solution described in step A2, and stir evenly to obtain an electrolyte.
[0059] Example 2
[0060] This embodiment provides an electrolyte and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the dosage of each component is different, as shown in Table 1, and the other conditions are the same.
[0061] Example 3
[0062] This embodiment provides an electrolyte and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the dosage of each component is different, as shown in Table 1, and the other conditions are the same.
[0063] Example 4
[0064] This embodiment provides an electrolyte and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the dosage of each component is different, as shown in Table 1, and the other conditions are the same.
[0065] Example 5
[0066] This embodiment provides an electrolyte and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the dosage of each component is different, as shown in Table 1, and the other conditions are the same.
[0067] Example 6
[0068] This embodiment provides an electrolyte and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the dosage of each component is different, as shown in Table 1, and the other conditions are the same.
[0069] Example 7
[0070] This embodiment provides an electrolyte and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the dosage of each component is different, as shown in Table 1, and the other conditions are the same.
[0071] Example 8
[0072] This embodiment provides an electrolyte and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the dosage of each component is different, as shown in Table 1, and the other conditions are the same.
[0073] Comparative Example 1
[0074] This comparative example provides an electrolyte and a preparation method thereof. The difference between this comparative example and Example 1 is that the dosage of each component is different, as shown in Table 1, and the other conditions are the same.
[0075] Comparative Example 2
[0076] This comparative example provides an electrolyte and a preparation method thereof. The difference between this comparative example and Example 1 is that the dosage of each component is different, as shown in Table 1, and the other conditions are the same.
[0077] Comparative Example 3
[0078] This comparative example provides an electrolyte and a preparation method thereof. The difference between this comparative example and Example 1 is that the dosage of each component is different, as shown in Table 1, and the other conditions are the same.
[0079] Comparative Example 4
[0080] This comparative example provides an electrolyte and a preparation method thereof. The difference between this comparative example and Example 1 is that succinonitrile (SN) is used to replace the cyanosiloxane multifunctional additive in Example 1, as shown in Table 1, and the other conditions are the same.
[0081] Test Case
[0082] The electrolyte prepared in the embodiment and the comparative example is injected into the NaNixFeyMn(1-xy)O2 / hard carbon cylindrical 21700 battery housing. The battery design capacity is 2.5Ah, and the injection coefficient is 3.6g / Ah. After the injection is completed, packaging, shelving, formation, aging, and capacity division are performed to obtain a sodium ion battery. After this lithium battery is divided into capacity, low temperature (-20°C), normal temperature (25°C) and high temperature (55°C) cycle performance tests are performed. The electrolyte prepared in the embodiment and the comparative example is injected into the NaNixFeyMn(1-xy)O2 / hard carbon soft package. The battery design capacity is 5Ah, and the injection coefficient is 3.8g / Ah. After the injection is completed, packaging, shelving, formation, secondary packaging, aging, and capacity division are performed to obtain a sodium ion battery. After this lithium battery is divided into capacity, a high temperature (55°C) cycle gas production test is performed.
[0083] Test conditions:
[0084] Normal temperature (25°C) and high temperature (55°C) cycle performance test charging and discharging test conditions: 1C constant current charging to 4.15V, constant voltage charging to cut-off current 0.02A, 1C discharge cut-off voltage 2.0V;
[0085] High temperature (55°C) cyclic gas generation performance test Charge and discharge test conditions: stand for 2h before charge and discharge, 1C constant current charge to 4.15V, constant voltage charge to cut-off current 0.02A, 1C discharge cut-off voltage 2.0V, cycle 500 times;
[0086] Low temperature (-20℃) cycle performance test charge and discharge test conditions: 1C constant current charge to 4.15V at room temperature, constant voltage charge to cut-off current 0.02A, 0.5C discharge cut-off voltage 2.0V at low temperature;
[0087] Table 1 Performance test of sodium ion batteries of embodiments and comparative examples.
[0088]
[0089] Among them, Examples 1-8, Comparative Examples 2 and 3 use 2-cyanoethyltriethoxysilane, and Comparative Example 4 uses succinonitrile SN. The sodium ion battery cycle test of the electrolyte of this system is carried out at low temperature, room temperature and high temperature respectively. The test results are shown in the table. Cyanosilane is used as a new functional electrolyte additive in high-voltage NaNi x Fe y Mn (1-x-y) O2 / hard carbon sodium ion battery can significantly improve its room temperature cycle capacity retention rate, low temperature discharge capacity retention rate and inhibit gas production under high temperature cycle, thus improving its comprehensive cycle performance. x Fe y Mn (1-x-y) The capacity retention rate of the O2 / hard carbon sodium ion battery after 1500 cycles increased from 66.20% to 85.8%. At 1C rate and 55°C, the volume expansion rate of the battery decreased from 15.1% to 3.8%. The improvement in cycle performance is mainly due to the fact that TDSTCN additives can undergo redox reactions before solvents, generating NaF-rich CEI and SEI films on the electrode, which not only have better interface stability, but also ensure higher ionic conductivity, thereby reducing interface impedance. The anionic groups of TDSTCN additives have high electronegativity and can be adsorbed on the surface of the positive electrode, reducing the contact area between the electrolyte and the positive electrode, and having a barrier effect; at the same time, there is a strong interaction between HF, capturing H protons, removing corrosive HF, reducing the decomposition of FEC, and inhibiting the corrosion of HF to the electrode material at a high voltage of 4.15V in sodium ion batteries. Inhibiting its interaction with NaNi x Fe y Mn (1-x-y) The side reaction of residual alkali on the surface of O2 active material and the side reaction with electrolyte inhibited the gas generation phenomenon, which was beneficial to NaNi x Fe y Mn (1-x-y) The structural stability of the O2 material prevents the phase transition from O3 to P2, further inhibiting the gas generation behavior. In addition, this type of additive reduces the active Na consumed by the destruction and repair of the SEI film. + , thereby increasing the reversible insertion and extraction of Na + The content reduces the number of defect sites in the hard carbon, reduces the adverse side reactions between the electrolyte and the hard carbon at the interface, maintains a relatively stable interface impedance of the negative electrode, improves the first coulomb efficiency of the hard carbon negative electrode, and improves the rate discharge cycle life of the layered oxygen system sodium ion battery.
[0090] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. An electrolyte for inhibiting cyclic gas production in a sodium ion battery, characterized in that: The raw materials for preparing the electrolyte include 80-85 parts of carbonate organic solvent, 0.5-5 parts of negative electrode film-forming additive, and 0.5-2.5 parts of cyanosiloxane multifunctional additive by weight; The structural formula of the cyanosiloxane multifunctional additive is shown in Formula I: R1, R2 and R3 are each independently selected from H, F, C1-C4 chain alkyl and C1-C4 perfluoroalkyl; 2. The electrolyte according to claim 1, characterized in that The cyanosiloxane multifunctional additive includes at least one of 2-cyanoethyltriethoxysilane, 3-diethoxysilylpropionitrile, 4-triethoxysilylbutyronitrile, 2-cyanoethylmethyldiethoxysilane, 3-(trimethoxysilyl)propionylnitrile, 3-propionitrile tributylmethoxysilane, 3-[tris(2,2,2-trifluoroethoxy)silyl]propionitrile and 5-triethoxysilylvaleronitrile.
3. The electrolyte according to claim 1, characterized in that The carbonate organic solvent includes at least one of cyclic carbonate and linear carbonate.
4. The electrolyte according to claim 3, characterized in that The cyclic carbonate includes at least one of ethylene carbonate and propylene carbonate; preferably, the linear carbonate includes at least one of diethyl carbonate and ethyl methyl carbonate.
5. The electrolyte according to claim 1, characterized in that The raw materials for preparing the electrolyte also include electrolyte sodium salt, and the electrolyte sodium salt includes: sodium hexafluorophosphate.
6. The electrolyte according to claim 5, characterized in that The raw materials for preparing the electrolyte include 80-85 parts of carbonate organic solvent, 10-15 parts of electrolyte sodium salt, 0.5-5 parts of negative electrode film-forming additive and 0.5-2.5 parts of cyanosiloxane multifunctional additive by weight.
7. A method for preparing an electrolyte according to any one of claims 1 to 6, characterized in that: The preparation method comprises mixing raw materials for preparing the electrolyte.
8. The preparation method according to claim 7, characterized in that: The mixing process is carried out in a glove box, and the environmental indicators in the glove box include: H2O<0.1ppm.
9. A sodium ion battery, characterized in that: The sodium ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte according to any one of claims 1 to 6.
10. The sodium ion battery according to claim 9, characterized in that: The positive electrode includes a layered oxide NaNi x Fe y Mn (1-x-y) O2; wherein, the value of x is 0.4~0.6, and the value of y is 0.2~0.4.